Anatomizing the robustness of multichannel MAC protocols for WSNs: An evaluation under MAC oriented design issues impacting QoS. (1st November 2018) - Rehan, Waqas; Fischer, Stefan; Rehan, Maaz
Abstract: Traditional Wireless Sensor Networks (WSNs) are single-channel based and mainly focus on energy-efficiency and scalability. Therefore, they may readily suffer from issues such as bandwidth insufficiency, interference, jamming and so on. With the deployment of dense sensor networks and the outset of multimedia technology, the intensity of the above-mentioned issues is further aggravated. To address those challenges, the researchers have employed multichannel technology in WSNs that focuses on increasing bandwidth/throughput while decreasing collision/congestion, delay, and energy consumption. For ascertaining a comprehensive exploration of multichannel technology in WSNs, this paper discusses in detail the important issues that are indispensable for providing high-performance and achieving Quality of Service (QoS) in multichannel WSNs. Further on, it evaluates a variety of multichannel MAC protocols under the stated design issues and classifies them into the categories Highly, Medium and Least-Robust, based upon aggregate-of-the-design-issues addressed by the corresponding multichannel MAC protocols for WSNs. Besides on the basis of channel access mechanism, each main category is sub-categorized into Time Division Multiple Access (TDMA), Carrier Sense Multiple Access (CSMA), Composite and Other-Novel classes whereby the functionality of the MAC protocols belonging to each class is briefly discussed along with relevant pros & cons. In addition to that, the survey delineates the implementation of the multichannel methodology in the emerging smart technologies of WSNs. In the end, future research directions are anticipated and a reasonable conclusion is put forth.